Early treatment failure during treatment of Plasmodium falciparum malaria with atovaquone-proguanil in the Republic of Ivory Coast - Wurtz Nathalie; Pascual Aurélie; Marin-Jauffre Adeline; Bouchiba Housem; Benoit Nicolas; Desbordes Marc; Martelloni Maryse; de Santi Vincent; Richa Georges; Taudon Nicolas; Pradines Bruno; Briolant Sébastien (Malaria Journal, 2012)
Abstract The increased spread of drug-resistant malaria highlights the need for alternative drugs for treatment and chemoprophylaxis. The combination of atovaquone‐proguanil (Malarone®) has shown high efficacy against Plasmodium falciparum with only mild side-effects. Treatment failures have been attributed to suboptimal dosages or to parasite resistance resulting from a point mutation in the cytochrome b gene. In this paper, a case of early treatment failure was reported in a patient treated with atovaquone-proguanil; this failure was not associated with a mutation in the parasite cytochrome b gene, with impaired drug bioavailability, or with re-infection.